Using fluid dynamic concepts to estimate species movement rates in terrestrial landscapes. (October 2018) - Jones, Thomas J.; Watts, Kevin; Whytock, Robin C.
Highlights: We present a framework linking fluid flow principles to ecological terms. Darcy's law of fluid flow could be used to estimate species movement rate. The use of a viscosity or mobility term makes the concepts species specific. This intuitive approach could be further expanded to 2D transport models. Abstract: Habitat loss and fragmentation threatens biodiversity and ecosystem function. 'Permeability' and 'connectivity' indices are used to estimate how individuals, populations or genes move spatially through a landscape. Yet, despite the analogies between landscape permeability and the physical definition of permeability (the ability for a porous media to transport a fluid), there have been few attempts to apply the physical concepts of permeability and fluid flow to problems in landscape movement ecology beyond some simple examples in the early literature. Here, we present a conceptual model linking physical principles to ecological terms and illustrate how concepts from Darcy's Law of fluid flow through porous media could be used to quantify species movement rates through a heterogeneous terrestrial landscape. Although further refinement is needed to take this concept to two dimensions and into a full predictive model, the approach presented shows promise for quantifying the relative impacts of landscape change (e.g. habitat fragmentation or creation) on species movement rates.